Ampliación de la distribución de Dinapate wrightii Horn (Coleoptera: Bostrichidae) en Baja Californi Sur, México - Falcón-Brindis, Armando; Palacios-Cardiel, Carlos; Jiménez Jiménez, María Luisa (Instituto de Ecología, A.C., 2016)
We report the presence of the giant palm borer Dinapate wrightii in an oasis of Baja California Sur, Mexico. This beetle is considered a serious pest of the native desert palms of California and Arizona, U.S. It was reported almost 8 decades ago only with the remains of a specimen collected at 500 km forward of the Baja California. This finding extends the range of the species and clarifies its distribution in Mexico.